2016
DOI: 10.4049/jimmunol.1501027
|View full text |Cite
|
Sign up to set email alerts
|

Fc Receptor–like 5 Expression Distinguishes Two Distinct Subsets of Human Circulating Tissue–like Memory B Cells

Abstract: Fc receptor–like (FCRL) 5 is a novel IgG binding protein expressed on B cells, with the capacity to regulate Ag receptor signaling. We assessed FCRL5 expression on circulating B cells from healthy donors and found that FCRL5+ cells are most enriched among atypical CD21−/lo/CD27− tissue-like memory (TLM) B cells, which are abnormally expanded in several autoimmune and infectious diseases. Using multicolor flow cytometry, FCRL5+ TLM cells were found to express more CD11c and several inhibitory receptors than did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 46 publications
8
64
1
Order By: Relevance
“…These results suggest the possibility of a functional heterogeneity among aMBCs differentiating within an individual. Relevant to these observations, Li et al (29) reported that FcRL5 expression distinguished two subsets of aMBCs in healthy individuals that have distinct gene expression profiles. FcRL5 + aMBCs expressed more CD11c and inhibitory receptors as compared to FcRL5 − aMBCs and responded poorly to multiple stimuli.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results suggest the possibility of a functional heterogeneity among aMBCs differentiating within an individual. Relevant to these observations, Li et al (29) reported that FcRL5 expression distinguished two subsets of aMBCs in healthy individuals that have distinct gene expression profiles. FcRL5 + aMBCs expressed more CD11c and inhibitory receptors as compared to FcRL5 − aMBCs and responded poorly to multiple stimuli.…”
Section: Introductionmentioning
confidence: 88%
“…T-bet has been detected in MBCs and plasmablasts in healthy adults, but at lower levels than other T-bet + lymphocytes (60). T-bet expression in circulating CD21 − CD27 − has been described in healthy adults, in whom CD21 − CD27 − B cells are a relatively rare population (8, 29) and T-bet + , CD11c + B cells appear to be expanded in healthy elderly individuals (61). But whether CD21-CD27 − T-bet + B cells in healthy adults represent the same population of CD21 − CD27 − T-bet + aMBCs that are expanded in settings of chronic infections remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CD85j lo B cells, the CD21 -Tbet -counterpart of our cells of interest, were more similar to the antigen-inexperienced subsets (naive, transitional; Figure 4B), suggesting these are relatively unrelated to T-bet hi CD85j hi cells and confirming the previously described population heterogeneity within the TLM phenotype (CD21 -CD27 -; ref. 40). We next set out to establish a functional connection between T-bet and the transcriptional targets it might regulate in T-bet hi population because they can be identified and sorted via negative selection, avoiding potential ligation effects of CD85j-specific antibodies.…”
Section: Absence Of Detectable Viremia In Ecs and Art Individuals Wasmentioning
confidence: 99%
“…TLM B cells tend to be enriched for polyreactivity and are expanded in several autoimmune diseases, suggesting this population may contribute to pathology [14,92,95]; however, polyreactivity has also been hypothesized to enhance antiviral humoral immunity and may be a beneficial property during antiviral responses [96]. Lastly, with regard to the aforementioned points, it becomes difficult to extrapolate from TLM B cell findings as most TLM B cell studies are complicated by CD21 − CD27 − population heterogeneity: we and others identified significant differences between the T-bet + and T-bet − subsets that together comprise the TLM B cell population [13,97], but studies have generally assessed the TLM population as a whole. Accordingly, additional studies are necessary to further define the stimuli that best activate T-bet + TLM B cells, the relationship of this population during HIV infection to its counterpart in non-inflamed individuals, and any potential role for T-bet + TLM B cells during HIV.…”
Section: T-bet and Tissue-like Memory B Cellsmentioning
confidence: 99%